Augmented Reality Portal 360 Degrees Tourism “Bundaran Balanga” Sampit - Minarni Minarni; Fery Setiawanto; Linda Norhan; Tedi Kustandi (Jurnal Mantik, 2021)
The tragedy that occurred in the Sampit area 20 years ago was commemorated and immortalized by the local government with the construction of the "Bundaran Balanga ". Initially, the roundabout was only a monument made of wood which became a symbol of peace which was later enhanced with typical Dayak ornaments which became historical tours for tourists. However, information about this history cannot be obtained by tourists or people who visit there or who want to visit the place because there is no media and supporting technology for this tour. A tourism application was made to introduce the history of the Balanga roundabout accompanied by Augmented Reality which can display a 360 degree view of the object. The data collection method is done by interview, documentation, observation and literature study. The stages of this research include concept, data collection, analysis and design, implementation and testing. This tourist application provides information about a complete description of the history of the Balanga Roundabout including the location and distance traveled along with photos. As for accessing Augmented Reality you have to scan the QR Code. This application helps provide information about the history of the Balanga Roundabout and tourists can feel as if they are in that location with a 360 degree view around it.